Mechanical Performance and Microscopic Mechanism of Coastal Cemented Soil Modified by Iron Tailings and Nano Silica - Xinjiang Song (MDPI AG, 2021)
In order to explore the effect of composite materials on the mechanical properties of coastal cement soil, cement soil samples with different iron tailings and nano silica contents were prepared, and unconfined compression and scanning electron microscope tests were carried out. The results show that: (1) The compressive strength of cement soil containing a small amount of iron tailings is improved, and the optimum content of iron tailings is 20%. (2) Nano silica can significantly improve the mechanical properties of iron tailings and cement soil (TCS). When the content of nano silica is 0.5%, 1.5%, and 2.5%, the unconfined compressive strength of nano silica- and iron tailings-modified cement soil (STCS) is 24%, 137%, and 323% higher than TCS, respectively. (3) Nano silica can promote the hydration reaction of cement and promote the cement hydration products to adhere to clay particles to form a relatively stable structure. At the same time, nano silica can fill the pores in TCS and improve the compactness of STCS.